Ownership and Changes in Hospital Inefficiency, 1986-1991 - Niccie L. McKay; Mary E. Deily; Fred H. Dorner (SAGE Publishing, 2002)
This study examines how ownership affected changes in hospital inefficiency after the introduction of prospective payment by Medicare. Using a national data set, we estimate cost frontiers for 1986 and 1991 to assess hospitals' efficiency relative to best practice in both those years. We then use regression analysis to determine the effect of ownership on the change in hospitals' efficiency. The results indicate that, in both 1986 and 1991, mean inefficiency was highest for for-profit hospitals and lowest for not-for-profit hospitals, with government hospitals falling in the middle. Moreover, between 1986 and 1991, both for-profit and government hospitals had significantly less improvement in efficiency than not-for-profit hospitals, all else equal.